INTERCULTURAL COMMUNICATION IN MULTICULTURAL SOCIETY (A STUDY ON THE ADAPTATION OF JAVANESE ETHNIC MIGRANT COMMUNITIES IN MATARAM UDIK VILLAGE) - Made Dewi Purnami; Tina Kartika, Nina Yudha Aryanti, Anna Gustina Zainal (Adisam Publisher, 2024)
The Balinese ethnic community has undergone transmigration due to the eruption of Mount Agung. Transmigration was carried out to Lampung Province, specifically in Central Lampung. This study aims to understand